EKSISTENSI KOMISI NASIONAL HAK ASASI MANUSIA DITINJAU DALAM SISTEM KETATANEGARAAN INDONESIA (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The existence of human rights values is a fundamental part of a country thatadheres to the concept of the rule of law (rechtstaat). Besides that human rights values are also regulated directly in the 1945 constitution. The birth of the National Human Rights Commission (Komnas HAM) is part of the long process of transitioning the Indonesian nation to a better direction in terms of increasing protection and upholding human rights in order to protect its people from arbitrary actions by the authorities. However, ironically, during the establishment of Komnas HAM, its current existence has not been able to have a positive and significant impact on the sustainability of human rights enforcement. The current limited powers, duties, and institutions have resulted in Komnas HAM not being able to optimally handle human rights issues, its existence is expected to be a bridge for enforcing and resolving allegations of gross human rights violations. Therefore, as a state of law that upholds the values of human rights, Komnas HAM needs special attention and a legal political attitude from the goverment and he people’s representative council. The purpose of this study was to determine the existence of Komnas HAM in terms of the Indonesian constitusional system and how the ideal model of Komnas HAM will be in the future. This research is a normative legal research. This is based on library research that takes quotes from reading books, or supporting books that have something to do with the problem to be studied. This study uses secondary data sources consisting of primary, secondary, and tertiary book materials. This study also uses qualitative data analysis and produces descriptive data.From the result of the research and discussion carried out, there are several conclusions obtained, namely : First, the currenct existence of Komnas HAM is still far from the expectations and spirit of enforcing human rigts, such as institutions, functions, and limited authority , resulting in the Komnas HAM institutions not being able to effectively enforce human rights. Maximally address human rights issues. Second, Komnas HAM must improve and establish synergy with state institutions such as the prosecutor’s office, the people’s representative council and the goverment, as well as invite community participation so that later they will be able to evercome human rights problems. The author’s suggestions, first, is that it is hoped that by strengthening the Komnas HAM institutions as a whole by making a separate law or law regarding the Komnas HAM institutions, so that later the functions and authorities of these state institutions become stronger, especially in the process of investigating, investigating, and prosecuting rights violations. Heavy human rights in the past and present can be handled properly, second, it is hoped that the participation of the goverment and people’s representative council, along with related parties such as Komnas HAM, the attorney general’s office and community participation will sit together to formulate the idea Komnas HAM in the future.Keywords : Komnas HAM – State Institutions – State Administration